The Molecular Pathophysiology of Psoriatic Arthritis—The Complex Interplay Between Genetic Predisposition, Epigenetics Factors, and the Microbiome - Carvalho, Ana L.; Hedrich, Christian M. (Frontiers in Molecular Biosciences, 2021)
Psoriasis is a symmetric autoimmune/inflammatory disease that primarily affects the skin. In a significant proportion of cases it is accompanied by arthritis that can affect any joint, the spine, and/or include enthesitis. Psoriasis and psoriatic arthritis are multifactor disorders characterized by aberrant immune responses in genetically susceptible individuals in the presence of additional (environmental) factors, including changes in microbiota and/or epigenetic marks. Epigenetic changes can be heritable or acquired (e.g. through changes in diet/microbiota or as a response to therapeutics) and, together with genetic factors, contribute to disease expression. In psoriasis, epigenetic alterations are mainly related to cell proliferation, cytokine signalling and microbial tolerance. Understanding the complex interplay between heritable and acquired pathomechanistic factors contributing to the development and maintenance of psoriasis is crucial for the identification and validation of diagnostic and predictive biomarkers, and the introduction of individualised effective and tolerable new treatments. This review summarizes the current understanding of immune activation, genetic and environmental factors that contribute to the pathogenesis of psoriatic arthritis. Particular focus is on the interactions between these factors to propose a multifactorial disease model.